2017
DOI: 10.1016/j.jelekin.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Robust estimation of average twitch contraction forces of populations of motor units in humans

Abstract: The characteristics of motor unit force twitch profiles provide important information for the understanding of the muscle force generation. The twitch force is commonly estimated with the spike-triggered averaging technique, which, despite the many limitations, has been important for clarifying central issues in force generation. In this study, we propose a new technique for the estimation of the average twitch profile of populations of motor units with uniform contractile properties. The method encompasses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…This reflects that in STA, the force produced by other motor units represents a noise term, and that magnitude of this noise increases with the number of motor units. Finally, the results indicated that the error in the estimated twitch half relaxation time was always substantially higher compared to the other twitch parameters (>30%; Figure 6), as previously reported (Negro and Orizio, 2017). Importantly, it should be noted that these results reflect conditions without motor unit synchronization, which, if present to a sufficient degree, further corrupts the twitch estimates by STA (Kutch et al, 2007;Taylor et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This reflects that in STA, the force produced by other motor units represents a noise term, and that magnitude of this noise increases with the number of motor units. Finally, the results indicated that the error in the estimated twitch half relaxation time was always substantially higher compared to the other twitch parameters (>30%; Figure 6), as previously reported (Negro and Orizio, 2017). Importantly, it should be noted that these results reflect conditions without motor unit synchronization, which, if present to a sufficient degree, further corrupts the twitch estimates by STA (Kutch et al, 2007;Taylor et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…A few alternative methods based on system identification techniques have been previously proposed to overcome the limitations of the traditional STA technique in human (Andreassen and Bar-On, 1983;Kutch et al, 2010;Lim et al, 1995;Orizio et al, 2016) and in animal recordings (Drzymała-Celichowska et al, 2016). Recently, an advanced method have been proposed and it has demonstrated the ability to accurately estimate the averaged twitch parameters of a relatively small population of motor units (Negro and Orizio, 2017). The method is based on a model-based deconvolution of the recorded force signal using the identified discharge times of a relatively small (tens) population of motor units.…”
Section: Discussionmentioning
confidence: 99%
“…) and the spike triggered averaging methods to estimate twitch characteristics (Kutch et al . ; Negro & Orizio, ) will also be highly advantageous. Overall, it will be important to apply these approaches in multiple muscles in the future, with the eventual goal of understanding the relationships between synaptic organization, motoneuron properties, and the diversity of the musculoskeletal system in both normal and pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, the development of extracellular array recordings of populations of spinal interneurons (AuYong et al 2011) can further deepen the insights for cellular mechanisms. For human studies, statistical approaches for human firing data to estimate the durations of AHPs ) and the spike triggered averaging methods to estimate twitch characteristics (Kutch et al 2010;Negro & Orizio, 2017) will also be highly advantageous. Overall, it will be important to apply these approaches in multiple muscles in the future, with the eventual goal of understanding the relationships between synaptic organization, motoneuron properties, and the diversity of the musculoskeletal system in both normal and pathological states.…”
Section: A Return To Parallel Animal and Human Investigationsmentioning
confidence: 99%
“…1A). This latter time interval is much longer than the former, i.e., approximately 100 ms in muscles of normal human hand [38], such as to allow for tremor-generating synchronization of motor neuron discharges at around 9 Hz.…”
Section: Afferent Inputs In Parkinsonian and Physiological Tremormentioning
confidence: 99%